Laboratory Determination of Seed Germination of Soybean Samples (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article Information about the ability of soybean samples to germinate in laboratory conditions, the energy of germination of seeds in 3 days and the degree of germination in 7 days.